The Modifying Role of Firm Size on the Relationship between Accounting Conservatism and Financial Constraints Evidence from Non-Financial Companies on the Amman Stock Exchange (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This research aimed to study the moderating effect of Size on the relationship between financial constraints and accounting conservatism in a sample of non-financial companies listed on the Amman Stock Exchange during the period from 2017 to 2024. Financial constraints were measured using the KZ model, and accounting conservatism using the Givoly and Hayan (2000) model. The study used company size as a moderating variable. Return on assets as a control variable. The researcher conducted the statistical tests using the Eviews13 software. The study found a statistically significant inverse effect of accounting conservatism on financial constraints before and after adding the control variable. It also found a non-significant inverse effect of company size on financial constraints before and after adding the control variables. Furthermore, the study found a non-significant moderating effect of company size on the relationship between accounting conservatism and financial constraints. However, the relationship became significant when the control variables were added, indicating that accounting conservatism leads to an increase in the financial constraints imposed on companies, but this effect is mitigated in larger companies.
Keywords: Accounting conservatism, financial constraints, Firm size.